Improving Students’ Speaking Skills: Effect of Varied Questioning Strategies in The Classroom - Satriani; Amiruddin; A, Marya; Fahira, Ainun (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The objective of this study was to see if employing various questioning strategies improves the speaking skills of first-year students at MTs As'adiyah Putri 1 Sengkang in terms of correctness, fluency, and comprehensibility. The pre-experimental approach was used in this study. The students at MTs As'adiyah Putri 1 Sengkang made up the majority of the population. This study used a purposive sampling strategy to select one class as the sample, class VII-A, which has 30 students in the 2020/2021 academic year, because students in that class had more knowledge than students in other classes. A test of learning outcomes was used, which included speaking skills (pre-test and post-test). The findings of this study reveal that the accuracy of the students' speaking has improved. The findings of the pre-test show that just 4% of students received a score of 71–85, but 24% of students received that score in the post-test. Furthermore, on both the pre-test and post-test, the percentage of pupils in the extremely bad group was 48 percent (0 percent). The value of the sig.2-tailed is not above the level of significance (0.000 < 0.05) and also proves it. After the test, the students' speaking skills increased to a good level in response to varied questioning strategies.